Od języka do literatury i od literatury do języka. O niektórych możliwościach integrowania kształcenia literackiego z językowym w edukacji polonistycznej - Kowalikowa, Jadwiga; Pachowicz, Małgorzata; Choińska, Krystyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Istnieją w obrębie dydaktyki polonistycznej zagadnienia, które nie przestają przyciągać uwagi wszystkich zainteresowanych problematyką edukacji. Do tych aktualnych zagadnień należy integrowanie kształcenia literackiego z językowym w edukacji polonistycznej. W artykule podjęto próbę aktualizacji „starej” metody tzw. sądu nad bohaterem literackim i przybliżenia nowej metody analizy dokumentacyjnej.

Integrating literary education with language education ranks among those research topics which invariably attract the attention of everyone interested in teaching. The authors of the paper aim to revisit an “old” method of literary analysis, namely, a “literary tribunal” over a literary protagonist, as well as to explore a different, “newer” method of teaching, namely a document analysis. Both methods reinforce the integrative character of education.
From Language to Literature and from Literature to Language. On Selected Strategies of Integrating Literary Education with Language Education
Keywords: integrowanie kształcenia literackiego z językowym; sąd literacki; metoda analizy dokumentacyjnej; integrating literary education with language education; literary tribunal; document analysis